A static object-oriented debugging model using Unified Modeling Language - Mohd Sani, Nor Fazlida; Mohd Ariffin, Noor Afiza; Atan, Rodziah
Debugging is one of a major task in programming. Although it’s kind of a complex cognitive activity, yet still one of the selected choices of solving programming errors. Main issues of current debugger is not suggested such solutions on how to fix an errors, especially on the logic errors. Besides that, learning on computer programming becomes more challenging. In addition, with paradigm such object-oriented programming concept, with incorrect logic of programming will bring to wrong output of the program itself. This foreword and backward process of finding logic errors in programming code such a very difficult task. Without tool such as debugger, it has been recognized as a component that can ease the process of finding errors in codes. Unfortunately, existing debugger component usually not pointing to exact LOC, which contains the logic error. In this research we’ll focuses on proposing new debugging model with static approach on pointing specific logic errors in an object-oriented programming code. The system model is created using the standard notation of object-oriented system called Unified Modeling Language (UML), since the proposed debugging model will be developed in the same environment. The result of this paper contains the UML model has been developed using the Unified Approach methodology.